The Effect of Training Models to Improve Smashes in Volleyball Games at RVS Kuamang Club - Hendra, Jhony; Kurniawan, Aan; Tri Susanti, Desi; Bani Pilitan, Raja; Trisnawati, Winda (Jurnal Performa Olahraga, 2026)
This study began with very poor training in carrying out various attack models, Players only rely on attacks from the front position with the limitations of the setter in organizing team attacks, so that smashes are easily blocked by opposing players, lack of training model strategies given by the coach during training. So that when participating in the match they always lose and have difficulty in fighting the opponent's playing pattern which is very accurate in carrying out attacks. This study aims to improve smash skills in volleyball at the RVS Kuamang Club. This study was conducted using an experimental method with a research design of "one group pre-test-post-test design". The population in this study were 24 members of the RVS Kuamang Club. The sample in the study amounted to 10 members according to the criteria determined by the researcher. The test instrument used was a smash ability test and a sampling technique with purposive sampling. The data analysis technique used a normality test and a hypothesis test (t-test). Based on the results of the study, the pre-test results were obtained with an average of 7.9 and the post-test results with an average of 16.9. Based on the test results, it shows that the t-count value (3.13) > t-table (1.83), thus Ha: accepted and H0: rejected. Based on the research results, it can be concluded that Ha "there is an influence of the training model to improve smashes in the RVS Kuamang club volleyball game".